Lack of association between genetic variations in CYP3A5 and blood pressure or hypertension risk in the UK biobank - Leibold, Pia; Lteif, Christelle; Duarte, Julio D. (Frontiers in Genetics, 2025)
IntroductionHypertension (HTN) is a leading risk factor for several cardiovascular diseases. While some previous studies reported that CYP3A5 variants were associated with decreased blood pressure and risk of HTN, others reported no associations. Therefore, we aimed to analyze these associations in the UK Biobank, a population large enough to have sufficient power to detect meaningful associations.MethodsThe association of CYP3A5 variants (*3, *6, *7) and CYP3A5 activity with systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and HTN diagnosis was analyzed in the UK Biobank (N = 487,171). Linear and logistic regression models were used, adjusting for age, sex, race, antihypertensives use, smoking status, and salt intake. Moreover, subgroup analyses were performed in Black participants, White participants, participants of East Asian and South Asian descent separately, using the same models.ResultsNeither the CYP3A5 variants, nor the CYP3A5 activity showed significant associations with SBP, DBP, MAP, or HTN. In a sensitivity analysis based on different racial subgroups, only White participants showed significant associations between the CYP3A5*3 variant and slightly higher DBP (β = 0.10 mmHg, 95% CI: 0.02 to 0.18, P = 0.01), as well as between genotype-predicted CYP3A5 activity score and slightly lower DBP (β = −0.10 mmHg, 95% CI: −0.18 to −0.02, P = 0.01). Discussion:While some associations were statistically significant, the small effect sizes and lack of associations observed in the whole UK Biobank population suggest that CYP3A5 variation likely has no impact on blood pressure related phenotypes in a general population.